Uterine rupture during pregnancy after laparoscopic myomectomy. - Akylbek Tusupkaliyev; Svetlana Tuitebayeva; Abai Nurken; Zhanargul Eshimbayeva; Leila Sarsembayeva (National Scientific Medical Center, 2017)
Hysteromyoma is one of the most common gynecological disease that occupies an important place among the pathologies of the reproductive system. One of the main objectives of conservative surgery is to preserve the reproductive function. Long-term consequences of the removal of myoma needs to be assessed in relation to pregnancy and childbirth. In classic case complications of uterine rupture disruption is internal bleeding and antenatal fetal death. We found a uterine rupture during pregnancy after laparoscopic myomectomy scar accompanied by bleeding and impaired fetal life. Description of the case, we would like to note to the possibility of uterine rupture disruption during pregnancy in women after conservative myomectomy by laparoscopic access, more careful outpatient observation and individual approach to the issue of the timing of delivery.